Malnutrition and associated variables in an elderly population of Criciúma, SC - Ribeiro,Rita Suselaine Vieira (2011)
OBJECTIVE: Determining malnutrition and associated variables in the elderly. METHODS: A cross-sectional study was conducted among elderly people vaccinated against influenza in order to evaluate their nutritional status. Nutritional assessment was performed with the Mini Nutritional Assessment. To verify association of studied variables with the outcome, odds ratios was estimated using multiple logistic regression. RESULTS: A total of 236 elderly patients were recruited. The Mini Nutritional Assessment identified three patients (1.3%) with malnutrition and 59 (25%) at risk of malnutrition. Factors with a positive association to the outcome were psychological stress or acute disease in the past three months, weight loss (< 3 kg) during the last three months and sores or skin ulcers. On the other hand, consuming two or more servings of fruits or vegetables daily, eating meat, fish or poultry every day and drinking more than three cups of fluids per day were negatively associated to malnutrition and risk of malnutrition. CONCLUSION: The low prevalence of malnutrition found in this study may be due to the study sample of elderly individuals in good health. Some factors related to a recent health problem (psychological stress or acute disease) seem to be positively associated while regular consumption of fluids and certain foods seem to be negatively associated with malnutrition.